2005
DOI: 10.1211/jpp.57.12.0010
|View full text |Cite
|
Sign up to set email alerts
|

The role of endothelin receptor antagonism in collar-induced intimal thickening and vascular reactivity changes in rabbits

Abstract: Intimal thickening, due to smooth muscle cell migration and proliferation, is considered to be one of the major components of vascular proliferative disorders such as atherosclerosis and restenosis. One experimental model, resulting in intimal thickening in the rabbit, involves placing a silicon collar around the carotid artery, and is used in this study. Endothelin is known to act as a strong mitogen and to stimulate smooth muscle cell proliferation and migration. We investigated the contribution of endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…[19][20][21] In our previous study, we demonstrated that endothelin contributes to the development of intimal thickening in the collar model and also that endothelin receptor antagonism had an inhibitory effect on thickening of intima. 22 In this study, using the same model, we aimed to investigate (1) the role of gelatinases (MMP-2 and MMP-9) in the development of collar-induced intimal thickening and (2) the effects of TAK-044 {cyclo [D-a-aspartyl-3-[(4-phenylpiperazin-1-yl) carbonyl]-L-alanyl-L-a-aspartyl-D-2-(2-thienyl) glycyl-L-leucyl-D-tryptophyl] disodium}, a nonselective ETA/ETB receptor antagonist, on the expression and activities of these enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] In our previous study, we demonstrated that endothelin contributes to the development of intimal thickening in the collar model and also that endothelin receptor antagonism had an inhibitory effect on thickening of intima. 22 In this study, using the same model, we aimed to investigate (1) the role of gelatinases (MMP-2 and MMP-9) in the development of collar-induced intimal thickening and (2) the effects of TAK-044 {cyclo [D-a-aspartyl-3-[(4-phenylpiperazin-1-yl) carbonyl]-L-alanyl-L-a-aspartyl-D-2-(2-thienyl) glycyl-L-leucyl-D-tryptophyl] disodium}, a nonselective ETA/ETB receptor antagonist, on the expression and activities of these enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…We ha ve al so shown that ET has an im por tant ro le in the prog res si on of in ti mal thic ke ning in this mo del and the non se lec ti ve en dot helin re cep tor an ta go nist TAK-044 in hi bi ted in ti mal thic ke ning, ge la ti na se up re gu la ti on and ac ti va ti on in col la red ar te ri es. 15,16 It is known that ge la ti na se up re gu la ti on in du ces deg ra da ti on of col la gen. Howe ver, in this study, col la gen con tent was not af- fec ted by TAK-044 tre at ment. The re fo re, this eviden ce sug gests that HSP47 and col la gen are expres sed in de pen dently from ET re cep tor-me di a ted cell sig na ling path ways in the col lar in du ced early at he rosc le ro sis mo del.…”
Section: Medical Pharmacologymentioning
confidence: 99%
“…We al so sho wed that a non se lec ti ve en dot he lin recep tor an ta go nist, TAK-044, in hi bi ted in ti mal thicke ning, MMP up re gu la ti on and ac ti va ti on in this mo del. 15,16 Thus, in this study, we ai med to in ves tiga te the pos sib le ro le of HSP47, the re la ti on betwe en HSP47 and col la gen sythe sis, and al so the ef fects of a non se lec ti ve ETA/ETB re cep tor an tago nist, TAK-044 in col lar-in du ced early at he roscle ro sis mo del.…”
mentioning
confidence: 97%
“…32 In this res pect, the inef fec ti ve ness of ni fe di pi ne may be cau sed by the inef fi ci ency of ni fe di pi ne on cyto ki nes, en dot he lin and/or ad he si on mo le cu les. 33,34 On the ot her hand, this study de mons tra ted that the re si du al lu men ra ti o and lu men pe ri me ter sig ni fi cantly dec re a sed and the lu men are a ten ded to be re du ced du e to col lar-in du ced in ti mal thic ke ning.…”
Section: Fi Gu Rementioning
confidence: 99%